Wave-Blocking Characteristics of Corrugated Plates under Explosion - Guoliang Yang; Shuai Feng; Wenjia Huang (Shock and Vibration)
Corrugated-board explosion-proof wall is the main means to prevent explosion shock wave damage, and it is important to study the effect of different corrugated plates on the shock wave. Using a high-speed schlieren experimental system and an air overpressure test system, the wave-blocking characteristics of different forms of corrugated plates are comprehensively studied. The schlieren images were used to analyze the influence that the corrugation shape of a corrugated plate has on the shock wave propagation characteristics. The results show that the reflection process of the triangular-, trapezoidal-, and half-cylindrical-shaped corrugated plates exhibit differences. The number of reflected waves from the triangular corrugated plate is much greater than that from the other corrugated plates, and it will consume more energy. The diffraction wave-front velocity has a trend of initially decreasing and then increasing and is also reduced by different degrees by the reflection. Comparative analysis of the schlieren images and the air shock wave overpressure test shows that plates corrugated with different corrugation shapes decrease the diffraction overpressure peak and exhibit a hysteresis.